2017
DOI: 10.4049/jimmunol.1700671
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Inhibit T Follicular Helper Cell Immune Response in Japanese Encephalitis Virus Infection

Abstract: Resolution of viral infections requires activation of innate cells to initiate and maintain adaptive immune responses. In this study, we examined Japanese encephalitis virus (JEV) infection leading to acute encephalopathy depending on suppression of the adaptive immune responses mediated by innate cells. Infection with P3 strains of JEV enhanced myeloid-derived suppressor cell (MDSC) populations, and the survival rate of JEV-infected mice improved after MDSC depletion. Mechanically, P3-induced MDSCs suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 73 publications
(81 reference statements)
2
25
0
Order By: Relevance
“…In addition, populations of mature activated suppressive neutrophils can be present in both the LDN and NDN fractions [63,72], or can be obtained by red blood cell lysis without performing density gradient centrifugation [73]. Mice: as observed in humans, pathogen infections of different types may induce the appearance of immature PMN-MDSCs with immunosuppressive functions in the circulation (LDNs/PMN-MDSCs) and infected tissues (PMN-MDSCs) [85][86][87][88]94]. In Staphylococcus aureus or Candida albicans models of infection, two subpopulations of neutrophils with opposite functions (proinflammatory, CD11b − CD49d + IL-12 + ; anti-inflammatory, CD11b + CD49d − IL-10 + ) have been identified [84].…”
Section: Mature Proinflammatory Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, populations of mature activated suppressive neutrophils can be present in both the LDN and NDN fractions [63,72], or can be obtained by red blood cell lysis without performing density gradient centrifugation [73]. Mice: as observed in humans, pathogen infections of different types may induce the appearance of immature PMN-MDSCs with immunosuppressive functions in the circulation (LDNs/PMN-MDSCs) and infected tissues (PMN-MDSCs) [85][86][87][88]94]. In Staphylococcus aureus or Candida albicans models of infection, two subpopulations of neutrophils with opposite functions (proinflammatory, CD11b − CD49d + IL-12 + ; anti-inflammatory, CD11b + CD49d − IL-10 + ) have been identified [84].…”
Section: Mature Proinflammatory Neutrophilsmentioning
confidence: 99%
“…As extensively reviewed elsewhere, pioneering papers have shown that different subpopulations of neutrophils develop (proinflammatory, CD11b − CD49d + IL-12 + ; anti-inflammatory, CD11b + CD49d − IL-10 + ), as in the case of methicillin-resistant S. aureus infections [14,84] (Figure 1). Recently, in mouse models of acute infection with Japanese encephalitis virus [85], chronic infection with Myobacterium tuberculosis [86], or in polymicrobial sepsis [87], populations of PMN-MDSCs were shown to inhibit CD4 + T cell proliferation and IFN-γ production, and also reduced differentiation and IL-21 production of T follicular helper cells, that in turn support pathogen immune evasion ( Figure 2). Moreover, pathogen dose can also be decisive during host defense, inducing neutrophils harboring opposite functions.…”
Section: Micementioning
confidence: 99%
“…Along with Tregs and IL-10, MDSCs were elevated in viral infection caused due to Japanese encephalitis virus (JEV). JEV induced MDSCs keep the potential to suppress T cells (specifically T[follicular]), splenic and plasma B cells ( 151 ) However, particular subset of MDSCs involved in infections caused by Vesicular stomatitis Indiana virus (VSV), adenovirus, Vaccinia, Pulmonary hypertension (PH), Chronic Obstructive Pulmonary Disease (COPD) is yet an enigma ( 152 154 ). Zang et al showed a positive correlation of MDSCs in patients with primary biliary cholangitis (PBC), a type of liver inflammation.…”
Section: Yin and Yang Arms Of Mdscsmentioning
confidence: 99%
“…A coevolution of Treg cells and CXCL-13 hi Tfh cells in the TLSs was found, with the ratio between these two populations being a critical factor for tumor control by benefiting the development of an anti-tumor humoral response ( 109 ). Furthermore, the presence of myeloid-derived suppressor cells within the LN could potentially be a negative regulator for Tfh cells ( 111 , 112 ), adding to the complexity of the regulation of these cells. Characterization of relevant cytokine producers and their spatial positioning within anatomically separated LN areas would be highly informative in understanding their potential role in regulating Tfh cell dynamics in SLN and TLSs.…”
Section: Lymph Nodes In Neoplasmsmentioning
confidence: 99%